Literature Review: Implementasi Teknik Role Playing dalam Konseling Kelompok untuk Mengembangkan Kecerdasan Emosional Siswa - Ramadhan Ramadhan; Muhammad Handi Pratama; Aisyah Nurbaiti; Ratna Sari Dewi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Emotional intelligence is an important aspect in students' personal and social development, as it affects their ability to understand and manage emotions, establish social relationships, and deal with academic pressures. One approach that can be used to develop students' emotional intelligence is to use group guidance services with the role playingmethod. This research uses the literature review method by collecting and analyzing various articles that discuss the application of the role playing method in group counseling services. This method allows students to play a role in a particular social situation so that they can practice expressing emotions, understanding other people's points of view, and developing interpersonal skills. The results show that role playing is effective in developing students' emotional awareness, empathy, and communication skills. Therefore, this method can be optimally applied by guidance and counseling teachers in supporting the development of students' emotional intelligence at school.